The Neoliberal Concept of Bulgarian Healthcare: Diversity or Cognitive Dissonance - Todorova, Elka; Chengelova, Emilia (Research Papers, 2023)
The paper examines the issue of the neoliberal nature of Bulgarian health care system, which introduced at once and in non-gradual way, formed varieties of combined neoliberal and anti-neoliberal theses. This is tracked in an analysis of data from ISSP surveys in Bulgaria (2021, 2022) regarding health care inequalities. Since the two surveys use certain identical questions, comparisons were made related to the performance and attitudes towards health care, vaccination, the role of the state authorities, etc. The results defend the thesis that neoliberal attitudes to health care are bend to nonliberal expectations in a way that exemplifies a type of “roll back” neoliberalism (Peck 2002).